Nixtamalization of durum wheat and the effect on protein secondary structure, gliadins, dough, and breadmaking quality - Rincón Aguirre, Alexandra; Figueroa-Cardenas, Juan de Dios; Ramírez Wong, Benjamín; Ibba, Maria Itria; Martinez Cruz, Eliel (Elsevier, 2022)
The objective of this study was to evaluate new nixtamalization approaches in durum wheat to overcome its rheological characteristics and poor breadmaking quality. To test this possibility, a durum-wheat variety was nixtamalized using either Calcium hydroxide [Ca(OH)2], calcium chloride (CaCl2), and calcium carbonate (CaCO3) at 0.3% and 0.7%. Nixtamalized durum wheat (NDW) dough using either CaCl2 or CaCO3, showed high elastic (storage) modulus (G′) and viscous (loss) modulus (G″), with dough elasticity values ranging from 10,000 to 35,000 Pa, which are appropriate for breadmaking. The FT-IR spectra showed that nixtamalized samples had in general higher antiparallel β-sheet values with samples treated with CaCl2 at 0.3% (37.29%), Ca(OH)2 at 0.3% (40.02%), and CaCO3 at 0.7% (39.55%) exhibiting the highest values. Bread from NDW exhibited significantly improved bread-loaf volume compared with non-nixtamalized the durum control, but not better crumb quality than the bread wheat control. Protein electrophoretic analysis demonstrated that after nixtamalization, new gliadin bands appeared in the region of the α-gliadins and ω-gliadins, which cannot be observed in the durum wheat without nixtamalization. To the best of our knowledge, this is the first study to investigate the effect of nixtamalization in durum wheat-dough composition, rheological quality, breadmaking potential, and protein structure.